2017
DOI: 10.1155/2017/7845963
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Abdominal Closure Is Safe and Effective: A Cohort Study in 74 Consecutive Patients

Abstract: Background Vacuum-assisted closure (VAC) has, in many instances, become the treatment of choice in patients with abdominal catastrophes. This study describes the use and outcome of ABThera KCI® VAC in the Region Southern Denmark covering a population of approximately 1.202 mill inhabitants. Method A prospective multicenter study including all patients treated with VAC during an eleven-month period. Results A total of 74 consecutive patients were included. Median age was 64.4 (9–89) years, 64% were men, and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…*SOFA score: 7 vs. 3, p = 0.037, 7 vs. 1, p < 0.001, 7 vs. PRE, p < 0.001, 3 vs. 1, p = 0.007, 3 vs. PRE, p < 0.001, 1 vs. PRE, p = 0.111; ** CRP: 7 vs. 3, p < 0.001, 7 vs. 1, p < 0.001, 7 vs. PRE, p < 0.001, 3 vs. 1, p < 0.001, 3 vs. PRE, p < 0.001, 1 vs. PRE, p = 1.0; ***PCT: 7 vs. 3, p < 0.001, 7 vs. 1, p < 0.001, 7 vs. PRE, p < 0.001, 3 vs. 1, p < 0. (Kafka-Ritsch et al, 2012;Bleszynski et al, 2016;Tartaglia et al, 2019) and some differ (Rezende-Neto et al, 2016;Jensen et al, 2017;Sartelli et al, 2019) from the current study. The important criteria for definitive closure included visual signs of intestinal viability, provision of full source control, no need for further surgical re-exploration, and no concerns for ACS (Rezende-Neto et al, 2016;Coccolini et al, 2018b;Sartelli et al, 2019).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…*SOFA score: 7 vs. 3, p = 0.037, 7 vs. 1, p < 0.001, 7 vs. PRE, p < 0.001, 3 vs. 1, p = 0.007, 3 vs. PRE, p < 0.001, 1 vs. PRE, p = 0.111; ** CRP: 7 vs. 3, p < 0.001, 7 vs. 1, p < 0.001, 7 vs. PRE, p < 0.001, 3 vs. 1, p < 0.001, 3 vs. PRE, p < 0.001, 1 vs. PRE, p = 1.0; ***PCT: 7 vs. 3, p < 0.001, 7 vs. 1, p < 0.001, 7 vs. PRE, p < 0.001, 3 vs. 1, p < 0. (Kafka-Ritsch et al, 2012;Bleszynski et al, 2016;Tartaglia et al, 2019) and some differ (Rezende-Neto et al, 2016;Jensen et al, 2017;Sartelli et al, 2019) from the current study. The important criteria for definitive closure included visual signs of intestinal viability, provision of full source control, no need for further surgical re-exploration, and no concerns for ACS (Rezende-Neto et al, 2016;Coccolini et al, 2018b;Sartelli et al, 2019).…”
Section: Discussioncontrasting
confidence: 73%
“…It was confirmed that the predominant source is from the lower GIT segments and that the microflora is associated with late colonisation, when a longer duration of the OA is needed (Rasilainen et al, 2015). The different bacteriologic pattern reported earlier may be explained by the large difference in patient cohorts and the traditional consumption of meat and animal fats (Carlson et al, 2013;Sartelli et al, 2014;Rasilainen et al, 2015;Jensen et al, 2017;Sartelli et al, 2017a). Several laboratory tests and scores are approved as effective criteria for the assessment of the clinical course of sepsis, including the biochemical markers of inflammation -CRP, PCT, the SOFA score and others (Schmit and Vincent, 2008;Cho and Choi, 2014;Sartelli et al, 2017b;Schmidt de Oliveira-Netto et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…VAMFT is a newer temporary abdominal closure technique that was introduced in the early 2000s, on the other hand, involves the use of a mesh material that is placed over the open abdomen and secured with suture. A vacuum device is then attached to the mesh, which creates negative pressure that helps to keep the abdominal contents in place and decrease the risk of herniation [4]. The mesh is placed over the area of interest and connected to the pump, which creates a vacuum that draws the mesh and the underlying tissue towards it.…”
mentioning
confidence: 99%